1993
DOI: 10.1002/ajmg.1320450203
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of the type I collagen genes

Abstract: The identification and functional analysis of DNA-protein interactions in the intronic and 5' flanking regions of the type I collagen genes has begun to define a series of cis-elements and trans-acting factors which regulate transcription of these genes. Studies such as these will eventually be expected to elucidate the mechanisms responsible for coordinate transcription of the alpha 1 and alpha 2 genes, a question which remains central to the field of collagen research. Although it is relatively straightforwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 119 publications
0
60
0
1
Order By: Relevance
“…Type I collagen, the most abundant mammalian collagen, consists of two ␣1(I) chains and one ␣2(I) chain that are coordinately expressed (1)(2)(3). Excessive deposition of type I collagen, characteristic of many fibrotic disorders (4), most likely results from transcriptional activation of collagen genes in response to cytokines and other factors present in prefibrotic/ inflammatory lesions.…”
mentioning
confidence: 99%
“…Type I collagen, the most abundant mammalian collagen, consists of two ␣1(I) chains and one ␣2(I) chain that are coordinately expressed (1)(2)(3). Excessive deposition of type I collagen, characteristic of many fibrotic disorders (4), most likely results from transcriptional activation of collagen genes in response to cytokines and other factors present in prefibrotic/ inflammatory lesions.…”
mentioning
confidence: 99%
“…A number of regulatory elements required for constitutive and inducible expressions have been identified in the promoter of both type I collagen genes (21,22). The previous studies have identified the ubiquitous factors, Sp1 and Sp3, and CBF/NF-Y and competitor (lane 1), and with nuclear extracts but without competitor (lanes 2 and 6).…”
Section: Discussionmentioning
confidence: 97%
“…Characterization of the cis-acting elements and trans-acting nuclear factors that modulate correct patterns of gene expression is necessary for understanding physiological and pathological conditions. Among the collagen genes, the transcriptional regulation of type I collagen has been most extensively studied, showing common features of the proximal promoter and tissue-specific enhancer (21,22). With regard to minor collagen, Penkov et al (23) identified the nuclear factors binding to the proximal promoter of COL5A2.…”
mentioning
confidence: 99%
“…Potential binding sites for AP2 havc been identified in the regulatory regions of the tnousc rrl(V1) (Bonaldo et al, 1993) and other collagcn genes (Slack et al, 1993), but actual binding of AP2 t o these sites has not heen demonstrated. 'The transcription factor AP2 is expressed in several embryonic tissues arid in the neural crest cell lineages during mouse embryogenesis (Mirchell el nl., 1991).…”
Section: Discussionmentioning
confidence: 99%